Comprehensive Generative Approach to Design Insoles - Schneider Julia; Essafi Sanae; Valerga Puerta Ana Pilar; Völz Diana (Current Directions in Biomedical Engineering)
Orthopaedic insoles are necessary for correcting foot deformities and providing customized support. This paper investigates the optimization of insole design through computational methods, with a focus on generative design (GD) techniques. By integrating advanced design methods with biomechanical analysis, this study aims to develop customized insoles that effectively treat foot disorders. To adequately account for all relevant forces acting on the foot during gait, a biomechanical load model is created. In addition to vertical forces, the model includes horizontal forces (anterior-posterior and medial-lateral) that occur parallel to the walking surface. GD can optimize the insole design to distribute pressure and support areas of the foot appropriately by creating functionally graded lattice structures. The study examines the potential of GD in creating insoles and the impact of the load model on the design outcome. The design process includes dynamic pedography and gait analysis to ensure that the insoles are tailored to the patient’s individual needs. Future research challenges include incorporating horizontal forces and minimizing mass while maintaining support. The study highlights the potential of computational methods, such as GD and artificial intelligence, in optimizing the design of orthopaedic insoles to ultimately improve patient comfort and mobility.